Content creation based learning: scholarship of teaching and learning - Hossein Karimi Moonaghi; Khatereh Shariati (Tabriz University of Medical Sciences, 2018)
Background: The performance of postgraduate students depends on a comprehensive combination of scientific and practical competencies acquired during their coursework. Identifying a teaching method that can promote learning outcomes, academic writing and, most importantly, content and knowledge creation will be valuable. Methods: Content creation based learning (CCBL) was used for a course in instructional design for 40 master's students in medical education. The project was implemented across four semesters over 2 years. Each semester included 17 two-hour sessions. CCBL includes the following steps: finding content about the subject of each session; summarizing, organizing and writing collected content; presenting content in classroom; receiving feedback from classmates and instructor; and revising the content produced. Results: The results are summarized as follows: (1) At the end of the course, 16 chapters of a valid and reliable book about instructional design could be produced. (2) The mean scores of student learning were 16.78 ± 1.3 (of a possible 20 points). This is a desirable level of learning. (3) The majority of students (60%) were highly satisfied. (4) Students felt this course had positive effects of this course on their academic achievement. Conclusion: The results of this scholarly activity revealed many practical issues in field of postgraduate education. Applying CCBL in postgraduate education is recommended. The researchers hope other studies about outcomes and efficacy of CCBL will provide more evidence.